2003
DOI: 10.1016/s1534-5807(03)00359-9
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Nonmuscle Myosin II Promotes the Asymmetric Segregation of Cell Fate Determinants by Cortical Exclusion Rather Than Active Transport

Abstract: Cell fate diversity can be achieved through the asymmetric segregation of cell fate determinants. In the Drosophila embryo, neuroblasts divide asymmetrically and in a stem cell fashion. The determinants Prospero and Numb localize in a basal crescent and are partitioned from neuroblasts to their daughters (GMCs). Here we show that nonmuscle myosin II regulates asymmetric cell division by an unexpected mechanism, excluding determinants from the apical cortex. Myosin II is activated by Rho kinase and restricted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
161
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(176 citation statements)
references
References 72 publications
14
161
1
Order By: Relevance
“…However, these studies also revealed that there was another unidentified Myosin that works synergistically with Lgl in the basal localization of cell fate determinants in larval neuroblasts. It was proposed that Lgl acts to restrict Myosin II to the apical cortex of neuroblasts during prometaphase and metaphase of mitosis, where it acts to exclude cell fate determinants (Barros et al, 2003), but given that Lgl has been shown to be excluded from the cortex at prometaphase in neuroblast cells of the sensory organ precursors (WirtzPeitz et al, 2008), it is unclear how Lgl can direct the localization of Myosin II to the apical region. Interestingly, in mammalian cells, aPKC activity seems to be required to phosphorylate and regulate Myosin IIB filament formation and subcellular localization (EvenFaitelson and Ravid, 2006;Rosenberg and Ravid, 2006).…”
Section: Scribble/dlg/lgl and Other Polarity Complexesmentioning
confidence: 99%
“…However, these studies also revealed that there was another unidentified Myosin that works synergistically with Lgl in the basal localization of cell fate determinants in larval neuroblasts. It was proposed that Lgl acts to restrict Myosin II to the apical cortex of neuroblasts during prometaphase and metaphase of mitosis, where it acts to exclude cell fate determinants (Barros et al, 2003), but given that Lgl has been shown to be excluded from the cortex at prometaphase in neuroblast cells of the sensory organ precursors (WirtzPeitz et al, 2008), it is unclear how Lgl can direct the localization of Myosin II to the apical region. Interestingly, in mammalian cells, aPKC activity seems to be required to phosphorylate and regulate Myosin IIB filament formation and subcellular localization (EvenFaitelson and Ravid, 2006;Rosenberg and Ravid, 2006).…”
Section: Scribble/dlg/lgl and Other Polarity Complexesmentioning
confidence: 99%
“…Because both yeast bud formation and epithelial polarity involve vectorial protein transport, it is appealing to consider that the nTSGs, and perhaps the entire polarity hierarchy, control polarity by regulating polarized vesicle trafficking. Alternative models have also been suggested, such as that the Lgl-myosin II interaction modifies the cortical cytoskeleton to prevent binding of cytoplasmic determinants (Barros et al 2003). Moreover, a role for the nTSGs in retention of previously localized proteins has not been ruled out.…”
Section: Polaritymentioning
confidence: 99%
“…Live imaging experiments clearly show that the cleavage furrow marker myosin is very dynamically localized during asymmetric cell division [Barros et al, 2003;Cabernard et al, 2010;Connell et al, 2011]. Previously, it has been reported that myosin is localized to the apical cortex during mitosis until anaphase [Barros et al, 2003].…”
Section: Cytokinesis In Asymmetrically Dividing Cellsmentioning
confidence: 99%
“…Previously, it has been reported that myosin is localized to the apical cortex during mitosis until anaphase [Barros et al, 2003]. However, recent live imaging experiments, using spindle and DNA markers to carefully time mitotic progression, revealed that by metaphase myosin is uniformly distributed on the cortex but disappears from the apical side shortly after anaphase onset.…”
Section: Cytokinesis In Asymmetrically Dividing Cellsmentioning
confidence: 99%